Literature Review: Crowdfunding and Political Fundraising - Ahmad, Saiful; Samputra, Palupi Lindiasari (Journal of Strategic and Global Studies, 2026)
Crowdfunding is an effort to raise relatively small amounts of money involving many individuals to support a specific project. Typically, crowdfunding is conducted online through fundraising platforms. The aim of this paper is to identify and analyse the utilisation of crowdfunding in fundraising activities that are related to or have political goals carried out by certain organisations or political groups. The method used in this paper is qualitative in the form of narrative analysis carried out through in-depth reading of several scientific literatures that discuss political fundraising through crowdfunding. The sources of scientific literature collection were obtained through the Google Scholar site by entering keywords that are relevant to the theme of discussion in this paper. The results obtained from this literature review show that the use of crowdfunding by political parties and political candidates is carried out in countries that already have an advanced democratic climate such as America and England and other European countries and India in Asia. The use of Crowdfunding was also found in fundraising for collective mass protests in Hong Kong which opposed state policies, as well as opposition movements in opposing rampant corruption in a country such as Russia.